أوضاع البحرية الجزائرية خلال العهد العثماني (1518-1830م) - لحسن ميهوبي; اشراف: مصطفى بن حسين (جامعة المسيلة كلية العلوم الانسانية والاجتماعية, 2026)
تتناول هذه الدراسة البحرية الجزائرية في العهد العثماني (1516-1830) كظاهرة تاريخية شاملة تجاوزت كونها مجرد قوة عسكرية. تتبع البحث نشأة البحرية منذ وصول الأخوين بربروس، مروراً بتطورها التنظيمي والإداري في عهدي البايات والدايات، وصولاً إلى أسباب انهيارها. كشفت الدراسة عن التنظيم المحكم للبحرية وأنظمتها المتطورة في التدريب والتسليح، ودورها كبوتقة انصهار اجتماعي جمعت عناصر متنوعة من أتراك وعرب وأندلسيين. على الصعيد المحلي، شكلت البحرية ركيزة السلطة السياسية والمصدر الرئيسي للدخل الاقتصادي، بينما لعبت دولياً دوراً محورياً في التضامن الإسلامي ومواجهة القوى الأوروبية. انتهت الدراسة بتحليل عوامل الضعف والانهيار، من التخلف التقني والضغوط الدولية إلى الصراعات الداخلية، مستخلصة دروساً حول أهمية القوة البحرية والتطور التقني والوحدة في حماية السيادة الوطنية. الكلمات المفتاحية: البحرية الجزائرية - العهد العثماني - الدايات - البايات - الأخوان بربروس - البحر المتوسط - طائفة الرياس - دار الصناعة البحرية - القرصنة - العلاقات الدولية - التنظيم الإداري - الجهاد البحري ________________________________________ Abstract This study examines the Algerian Navy during the Ottoman period (1516-1830) as a comprehensive historical phenomenon that transcended its role as merely a military force. The research traces the navy's establishment since the arrival of the Barbarossa brothers, through its organizational and administrative development during the Beylerbeyi and Dey periods, to the causes of its collapse. The study reveals the navy's sophisticated organization and advanced systems in training and armament, and its role as a social melting pot that brought together diverse elements of Turks, Arabs, and Andalusians. Locally, the navy formed the pillar of political authority and the main source of economic income, while internationally it played a pivotal role in Islamic solidarity and confronting European powers. The study concludes by analyzing the factors of weakness and collapse, from technical backwardness and international pressures to internal conflicts, drawing lessons about the importance of naval power, technical development, and unity in protecting national sovereignty. Keywords: Algerian Navy - Ottoman Period - Deys - Beylerbeys - Barbarossa Brothers - Mediterranean Sea - Raïs Corporation - Naval Arsenal - Piracy - International Relations - Administrative Organization - Naval Jihad